Technical-tactical performance in Greco-Roman wrestling: analysis of 2013 senior world championships through multivariate analysis - López González, D. E. (International Journal of Wrestling Science, 2014)
Using multivariate statistical procedures (Exploratory Factor Analysis, Hierarchical Clustering, and Discriminant Analysis by the Stepwise Method) to analyze values from a set of 14 technical-tactical performance indicators obtained through Notational Analysis video review, N=42 outstanding international level wrestlers samples were characterized and classified. The study group was composed of the wrestlers who achieved the top 5 placements in each of the seven weight categories at the Senior World Championships held in September of 2013, under the rule amendments proclaimed in May by the International Federation of Associated Wrestling Styles (FILA). Eight clusters solutions were chosen, finding significant contrast among specific indicators of offense and diversified technical resources in the par-terre position as main discriminant variables, as well as the frequency of successful techniques, set-up distance, offensive attitude and tactical risk rate in the standing position as complementary discriminant variables, which allowed for the correct classification of 95.2% of the cases. These findings can be highly relevant in providing specific guidance to coaches and wrestlers in order to adapt and model their strategies for the upcoming key events of 2013-2016 Olympic cycle. Additionally, the procedure conducted with Dartfish Team Pro 7 video analysis software, and the updated open access video files from access FILA´s WebTV videos repository, can be reproduced by trained analysts around the world.